2017
DOI: 10.1002/ajmg.b.32548
|View full text |Cite
|
Sign up to set email alerts
|

The use of electronic health records for psychiatric phenotyping and genomics

Abstract: The widespread adoption of electronic health record (EHRs) in healthcare systems has created a vast and continuously growing resource of clinical data and provides new opportunities for population-based research. In particular, the linking of EHRs to biospecimens and genomic data in biobanks may help address what has become a rate-limiting study for genetic research: the need for large sample sizes. The principal roadblock to capitalizing on these resources is the need to establish the validity of phenotypes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 76 publications
2
80
0
Order By: Relevance
“…Moreover, we were able to examine simultaneously genomewide associations with several other PTSD phenotypes reflecting various aspects of symptom type and severity, respectively. These data highlight the tremendous scientific value of EHR-based biobanks and automated phenotyping for genomic research Smoller, 2018), and even more so, the value of collecting relevant self-report data such as the PCL. Biobanks have specific subject and ascertainment characteristics; the nature of the MVP makes it uniquely suitable for study of PTSD, a disorder that occurs at increased rates in military veterans.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, we were able to examine simultaneously genomewide associations with several other PTSD phenotypes reflecting various aspects of symptom type and severity, respectively. These data highlight the tremendous scientific value of EHR-based biobanks and automated phenotyping for genomic research Smoller, 2018), and even more so, the value of collecting relevant self-report data such as the PCL. Biobanks have specific subject and ascertainment characteristics; the nature of the MVP makes it uniquely suitable for study of PTSD, a disorder that occurs at increased rates in military veterans.…”
Section: Discussionmentioning
confidence: 97%
“…Additional post-GWAS analyses included enrichment (tissue; pathway) and transcriptome-wide (Gamazon et al, 2015) analyses. Phenome-wide analysis (PheWAS) was conducted for the top GWAS hits against the VA-MVP EHR (Bush et al, 2016;Smoller, 2018) and possible drug candidates for repositioning were identified using publicly available drug-genomic databases.…”
Section: Introductionmentioning
confidence: 99%
“…While not a primary aim for some of these efforts, they all facilitate an increase in the number of patients that obtain a molecular diagnosis, thus creating a new opportunity to develop an infrastructure that supports formalising clinician-driven patient outcome registries to maintain careful phenotyping and prospectively report treatment outcomes linked to individuals with secure molecular diagnoses. Such standardised registries will empower large-scale studies investigating the extent of genotype-phenotype correlations within individual epilepsy genes and the relationships between molecular diagnoses and existing/novel therapeutic compounds [26]. The expert curation of patient-ascertained presumed pathogenic variants will also be of major research value since a more complete knowledge of the full disease-associated allelic series in epilepsy genes will facilitate appropriate research-driven functional studies.…”
Section: The Genetic Overlap Between Rare and Common Epilepsies Provimentioning
confidence: 99%
“…For example, an individual's health care may cross multiple organisational boundaries and hence involve multiple EHR instances. Furthermore, the validity of the phenotypes may be uncertain if the query used in the EHR-based case ascertainment is not appropriately defined [26]. These challenges are not insurmountable, but must be considered when exploiting EHR technology to enhance genomic medicine.…”
Section: Ehealth As a Catalyst For Precision Therapeuticsmentioning
confidence: 99%
“…We recently established the PsycheMERGE consortium within the NIH-funded Electronic Medical Records and Genomics (eMERGE) Network 15,16 to leverage electronic health record (EHR) data linked to genomic data to facilitate psychiatric genetic research 17 . In this first report from PsycheMERGE, we evaluated the performance of a schizophrenia PRS generated from summary statistics published by the Psychiatric Genomics Consortium 14 using EHR data on more than 100,000 patients from four large healthcare systems (Geisinger Health System, Mount Sinai Health System, Partners Healthcare System, and Vanderbilt University Medical Center).…”
Section: Introductionmentioning
confidence: 99%